Populist Parties and Pork-Barrel Politics in Indonesia: The Erosion of Political Morality - Jubaidi, Didi; Khoirunnisa, Khoirunnisa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The phenomenon of populist parties and